KONSEP TOLERANSI BERAGAMA MENURUT K.H ABDURRAHMAN WAHID DAN IMPLIKASINYA DALAM PEMBELAJARAN PAI - Ilham Arif Pebriansyah, - (2021)
Indonesia is a vast country and there are plurality and differences in race, culture, ethnicity, language and religion. From these differences we can make differences of opinion which are needed to understand and respect each other. Therefore, it is necessary to integrate religious tolerance into education in order to create harmony between religious communities. Therefore, it is necessary that the concept of good tolerance needs to be known from an early age, especially for students at every level in accordance with the conditions in Indonesia as a solution to the problem. This study aims to describe the concept of religious tolerance according to KH Abdurrahman Wahid which is implied in Islamic Education learning. This research uses a qualitative approach. In this research, the researcher himself becomes the research instrument. Collecting data in this study used library research techniques, while research data analysis was carried out by reducing data, presenting data, and drawing conclusions or verification from several premiere books and journals such as. From this research, the following results are obtained: (1) KH Abdurrahman Wahid integrates religion and state so that the concept of religious tolerance occurs to foster a sense of belonging as the responsibility of each religious adherent to maintain and strengthen diversity. (2) From this research, it can be found that the implications of the concept of tolerance in Islamic religious education are that students must think positively towards others who are different, do not justify themselves, respect differences and maintain diversity. The implication of the concept of religious tolerance is very relevant to the 1945 Constitution. 2 which reads: "The state guarantees the freedom of every citizen to embrace his or her own religion and to worship according to that religion". Keywords: Tolerance, Religious Tolerance, Harmony, Education